THE ROLE OF INTERPERSONAL COMMUNICATION ON EMPLOYEE PERFORMANCE PRODUCTIVITY - Imatun Saadia; Naylal Fithri; Muhammad Noor Busthomi; Maysara (International Journal of Multidisciplinary Reseach, 2026)
Interpersonal communication plays a crucial role in improving employee performance. Effective communication enables employees to clearly understand tasks, reduces misunderstandings, and increases motivation and work productivity. However, communication barriers in the workplace persist, such as a lack of openness and minimal feedback. Interpersonal communication has a positive and significant impact on employee performance because it creates a positive work climate, improves task understanding, reduces misunderstandings, builds trust, and encourages effective collaboration. Good communication quality, characterized by clarity of messages, openness, mutual respect, and feedback, enables employees to work more productively and motivated, ultimately contributing to improved overall performance. Studies indicate that up to 70% of workplace errors can be caused by poor communication between employees. These studies confirm that ineffective interpersonal communication can be a significant barrier to achieving organizational goals. The purpose of this study is to explore the direct impact of interpersonal communication on employee productivity and to provide practical guidance for management in improving communication dynamics in the workplace. The results demonstrate that interpersonal communication is a foundation for employee productivity, a crucial aspect for developing effective Human Resource Management strategies.